About duality in selected Polish translations of Slovenian prose - Gawlak, Monika (Slavia Centralis, 2021)
The article discusses attempts to transfer meanings contained in the grammatical category of dual based on selected translations of prose from Slovenian into Polish. Translators choose different solutions: reduction to the plural, resulting in a change in grammatical and semantic information; introduction of explicit information about the presence of the dual forms; or substitution and explication. Having added information about dual, the translator contributes to a transcultural process in which the translation is involved. It leaves a trace of the meeting between two different grammatical systems and creates a transcultural dimension to the translation.
Keywords: Joanna Pomorska; Polish translation; dual; Slovenian prose; cultural transfer